CYTOTOXIC EFFECTS OF ETHYL ACETATE FRACTIONS FROM SECONDARY METABOLITES OF STREPTOMYCES SP. GMY01 ON HUMAN BREAST CANCER MCF7 CELL LINES - Werdyani, Sista; Wijayanti, Nastiti; Fitria, Annisa; Rahmawati, Sari (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This research aimed to fractionate the ethyl acetate extract from secondary metabolites of Streptomyces sp. GMY01 and to identify which fraction contains cytotoxic active compounds against human breast cancer MCF7 cell lines. Methods: Secondary metabolites were obtained from fermentation of Streptomyces Sp. GMY01 for 15 d. The supernatant containing these secondary metabolites was extracted through partition using ethyl acetate as the solvent. Fractionation of the ethyl acetate extract was conducted via column chromatography using silica gel as the solid phase while the gradient mobile phase consisted of n-hexane, ethyl acetate, and methanol. The cytotoxicity of each fraction was calculated using MTT-assay. Results: The ethyl acetate extract could be separated into 9 fractions using column chromatography. The cytotoxic effect of each fraction differed from each other. The smallest IC50 value was obtained from fraction 4. Further investigation should be conducted to discover the active anticancer compound. The active compound with cytotoxic effect was found in fraction 4 because of the highest IC50 value. Conclusion: This fraction is potential to be investigated more deeply as anticancer, especially for breast cancer.